The «bellies for rent». Debates and reflections from feminist criticism - Posada Kubissa, Luisa (EUNOMÍA. Revista en Cultura de la Legalidad, 2021)
This article wants to participate in the current debate on the so-called «surrogate motherhood», which is here conceptualized rather as «bellies for rent». To do this, it reviews the main arguments for and against this practice in order to situate this current debate. From there, this work reaches its own conclusions, which are inscribed in the critical-feminist perspective. And it comes to the conclusion that this practice and the defense of its regulation constitute a reinforcement of the patriarchal system. A reinforcement that, in conjunction with the reigning neoliberal order, contributes today to nothing else but to deepen the position of inequality of women in our world.